Development of Atherosclerotic Cardiovascular Mortality in Gouty Arthritis and Rheumatoid Arthritis Patients: Are They Associated With Mean Platelet Volume and Neutrophil-Lymphocyte Ratio? A Comparative Study - Muhammet MADEN,; Gülsüm Emel PAMUK,; Ömer Nuri PAMUK, (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate the mean platelet volume (MPV) and neutrophil-lymphocyte ratio (NLR) in gouty arthritis (GA) and rheumatoid arthritis (RA) patients, as well as their relationship with atherosclerotic cardiovascular mortality (ACVM). Patients and methods: The study included 122 GA patients (96 males, 26 females; mean age 64.6±13.4 years; range 34 to 82 years), 82 RA patients (40 males, 42 females; mean age 62.1±12.1 years; range 29 to 83 years), and 61 healthy controls (34 males, 27 females; mean age 65.3±4.8 years; range 33 to 80 years). Clinical and ACVM data were obtained from medical charts. Erythrocyte sedimentation rate, C-reactive protein, MPV, and NLR were recorded at the time of diagnosis and one month after therapy. Results: Mean platelet volume in GA (8.49±1.5) and RA (7.98±0.99) groups were significantly lower than in healthy controls (9.8±15) (p<0.001). NLR in healthy controls (1.9±0.74) was significantly lower than in GA (3.6±2.3) and RA (3.7±2.5) groups (p<0.001). After treatment, MPV did not change significantly in GA and RA groups (p values >0.05); however, NLR decreased in both groups (p<0.001). Nine GA and 12 RA patients died from ACVM during follow-up. GA patients with ACVM were older and had more frequent hypertension, higher MPV, and higher intercritical CRP level. In multivariate analysis, MPV was an independent poor prognostic factor for ACVM in GA patients. Conclusion: Gouty arthritis and RA patients had significantly lower MPV and significantly higher NLR than controls. MPV might be used as a potential biomarker for the development of ACVM in GA.